Improved ethyl cellulose consolidant, method of making and use in iron salt photopaper consolidation

CN118979410BActive Publication Date: 2026-10-23SHAANXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411108535.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2026-10-23
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

[0006]针对现有纸张加固剂会导致图纸的颜色变化的技术问题,本发明提供一种改良乙基纤维素加固剂及其制备方法和在铁盐晒图纸加固中的应用

Benefits of technology

[0020] 1. The modified ethyl cellulose reinforcing agent provided by the present invention can effectively inhibit the color change of iron salt blueprint paper through the interaction of ethyl cellulose, organic solvent and antioxidant. When used in iron salt blueprint paper, the color difference value of iron salt blueprint paper after aging is as low as 1.74.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118979410B_ABST
    Figure CN118979410B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of archives protection, and relates to an improved ethyl cellulose reinforcing agent, a preparation method thereof and application of the improved ethyl cellulose reinforcing agent in iron salt photopaper reinforcement. The improved ethyl cellulose reinforcing agent is composed of ethyl cellulose, an organic solvent and an antioxidant. The mass-volume ratio of the ethyl cellulose, the organic solvent and the antioxidant is 0.9g:3ml:15uL-50uL. The organic solvent is a mixture of ethyl acetate, acetone and n-butanol in a certain proportion. The improved ethyl cellulose reinforcing agent is formed by the ethyl cellulose, the organic solvent and the antioxidant, can inhibit the color change of the iron salt photopaper, has hydrophobic performance, and has a good reinforcing and protective effect on the iron salt photopaper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of archival preservation technology, and relates to a modified ethyl cellulose reinforcing agent, its preparation method, and its application in the reinforcement of iron salt blueprint paper. Background Technology

[0002] Blueprints are an important part of archives, and the important engineering drawings recorded on them are an indispensable archival treasure. Effectively preserving these blueprints is one of the tasks of archive management. However, some blueprints are of considerable age and unstable nature. Therefore, by studying the nature of blueprints and properly preserving them, their use value and lifespan can be extended to the maximum extent. Although my country has carried out extensive work on the restoration and preservation of other paper artifacts for a long time, research on the preservation of blueprint archives is scarce. Many precious blueprints suffer from severe fading and blurred writing, and these problems have not been completely resolved. Traditional methods have not fundamentally and effectively protected these blueprint archives. Therefore, researching new, efficient, and practical methods for the preservation of blueprint archives is an urgent task.

[0003] Currently, diazo salt blueprints are the most commonly used blueprints on the market, so most of them are designed for the protection of such blueprints. However, there is no relevant literature on the reinforcement and protection of ferric salt blueprints, indicating that the protection of ferric salt blueprints is a completely new direction.

[0004] Common paper reinforcement methods include mounting, silk screen reinforcement, and protective liquid reinforcement. Mounting is a traditional paper reinforcement method unique to my country, often used to protect precious calligraphy and paintings. Its process is complex and requires highly skilled technicians, making it unsuitable for large-scale preservation of ordinary paper artifacts and archives. Silk screen reinforcement involves bonding silk mesh or other silk fabrics to the paper artifact. It is more suitable for reinforcing curled or fragile paper, but silk protein can easily breed bacteria, causing secondary damage to the paper artifact. Protective liquid reinforcement involves applying a reinforcing agent to the surface of the artifact to form a protective film, improving its mechanical properties, aging resistance, and durability. The process is simple and reversible.

[0005] Existing paper strengthening agents include polymethyl methacrylate (PMMA), fluoropolymers, and ethyl cellulose. PMMA is a thermoplastic polymer compound that can form a colorless and transparent protective film when coated on the surface of paper artifacts. It has a certain degree of water resistance, but its reversibility is poor and it is easily flammable. Fluoropolymers have advantages such as corrosion resistance, aging resistance, and light resistance. However, fluoropolymers have a large molecular weight, resulting in poor permeability and wettability. The strengthening agent does not easily penetrate into the paper fibers and can easily create a concentration gradient between the surface and the interior of the paper, which can lead to color changes in the paper and accelerate paper aging. Summary of the Invention

[0006] To address the technical problem that existing paper reinforcing agents cause color changes in drawings, this invention provides a modified ethyl cellulose reinforcing agent, its preparation method, and its application in reinforcing iron salt blueprint paper.

[0007] This invention forms a modified ethyl cellulose reinforcing agent through ethyl cellulose, organic solvents and antioxidants, which can inhibit the color change of iron salt blueprint paper and has hydrophobic properties, thus providing excellent reinforcement and protection for iron salt blueprint paper.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0009] A modified ethyl cellulose reinforcing agent is composed of ethyl cellulose, an organic solvent, and an antioxidant; the mass-volume ratio of the ethyl cellulose, organic solvent, and antioxidant is 0.9 g: 3 ml: 15 μL to 50 μL.

[0010] Further specifying, the organic solvent is a mixture of ethyl acetate, acetone and n-butanol in equal volumes.

[0011] Further specifying, the antioxidant is diphenylisooctyl phosphite, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butyl)phosphite, or triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate.

[0012] The preparation method of the modified ethyl cellulose reinforcing agent as described above includes the following steps:

[0013] S1. Mix ethyl cellulose and an organic solvent, and under stirring conditions, use the reflux method to completely dissolve the ethyl cellulose to obtain an ethyl cellulose solution.

[0014] S2. Add antioxidant to ethyl cellulose solution, heat and stir to mix evenly to obtain a reinforcing agent.

[0015] Further specifying, in step S1, the reflux temperature is 45℃~55℃, and the stirring speed is 300r / min~400r / min.

[0016] Further specifying, in step S2, the heating temperature is between 35℃ and 40℃, and the stirring speed is between 200 r / min and 300 r / min.

[0017] The application of the modified ethyl cellulose reinforcing agent provided by this invention in the reinforcement and protection of iron salt blueprint paper.

[0018] Furthermore, the modified ethyl cellulose reinforcing agent enables the color difference value of the iron salt blueprint paper to reach a minimum of 1.74 after aging.

[0019] The beneficial effects of the technical solution of this invention are:

[0020] 1. The modified ethyl cellulose reinforcing agent provided by the present invention can effectively inhibit the color change of iron salt blueprint paper through the interaction of ethyl cellulose, organic solvent and antioxidant. When used in iron salt blueprint paper, the color difference value of iron salt blueprint paper after aging is as low as 1.74.

[0021] 2. The modified ethyl cellulose reinforcing agent provided by this invention significantly enhances the hydrophobicity of blueprint samples after treatment; making them less susceptible to structural damage by water molecules during long-term storage, thus avoiding a series of problems such as bleeding, blurring, and smudging of the blueprint content, which would destroy the historical and cultural information they carry.

[0022] 3. In this invention, ethyl cellulose can enhance the hydrogen bonds between fibers, thereby improving the mechanical properties of paper, while the antioxidant DPOP can protect the paper under aging conditions and improve the weather resistance of blueprint paper.

[0023] 4. The modified ethyl cellulose reinforcing agent provided by this invention has a good mitigating effect on the reduction of whiteness value in blueprint paper. Attached Figure Description

[0024] Figure 1 The TG curves of five groups of films with different reinforcing agents are shown.

[0025] Figure 2 The whiteness changes of six groups of blueprinted papers with different treatments before and after aging;

[0026] Figure 3 The infrared spectra of six groups of blueprint paper with different treatments before and after aging are shown (a is the infrared spectrum before and after ethyl cellulose treatment, b, c, d, e, f are the infrared spectra of blueprint paper before and after aging (b: sample 1; c: sample 2; d: sample 3; e: sample 4; f: sample 5)).

[0027] Figure 4 Scanning electron microscope (SEM) images of six groups of blueprinted paper with different treatments before and after aging (a1, a2 are sample 1; b1, b2 are sample 2; c1, c2 are sample 3; d1, d2 are sample 4; e1, e2 are sample 5).

[0028] Figure 5 The changes in folding endurance of six groups of blueprinted papers with different treatments before and after aging;

[0029] Figure 6 The changes in tensile strength of six groups of blueprinted papers with different treatments before and after aging;

[0030] Figure 7 The changes in contact angle of six groups of blueprinted papers with different treatments before and after aging;

[0031] Figure 8 Changes in whiteness of blueprint paper before and after aging when different antioxidants are applied. Detailed Implementation

[0032] The technical solutions protected by this invention will now be described in detail with reference to the accompanying drawings and embodiments. However, it is obvious that the described embodiments are only some, not all, of the embodiments described herein. All other embodiments obtained by those skilled in the art based on the described embodiments without creative effort are within the scope of protection of this application.

[0033] This invention provides a blueprint paper reinforcement agent, which is composed of ethyl cellulose, organic solvent and antioxidant; the mass-volume ratio of the ethyl cellulose, organic solvent and antioxidant is 0.9g:3ml:15μL~50μL.

[0034] Preferably, the organic solvent is a mixture of equal volumes of ethyl acetate, acetone, and n-butanol.

[0035] In this invention, the antioxidants are diphenyl isooctyl phosphite (antioxidant DPOP), pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010), n-octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), tris(2,4-di-tert-butyl)phosphite (antioxidant 168), and triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate (antioxidant XH-245).

[0036] This invention also provides a method for preparing a modified ethyl cellulose reinforcing agent, comprising the following steps:

[0037] S1. Mix ethyl cellulose and organic solvent, and under stirring conditions, completely dissolve ethyl cellulose by reflux to obtain an ethyl cellulose solution. In step S1, the reflux temperature is 45℃~55℃, and the stirring speed is 300r / min~400r / min.

[0038] S2. Add antioxidant to ethyl cellulose solution, heat and stir until homogeneous to obtain the reinforcing agent. The heating temperature is 35℃~40℃, and the stirring speed is 200r / min~300r / min.

[0039] The blueprint paper reinforcing agent obtained by this invention enables the color difference value of iron salt blueprint paper after aging to reach as low as 1.74, effectively inhibiting the color change of iron salt blueprint paper. It also has hydrophobic properties, as well as good mechanical properties, heat resistance and anti-aging properties, and can be used as a reinforcing material in iron salt blueprint paper.

[0040] The present invention will now be described in detail with reference to specific embodiments.

[0041] It should be noted that, unless otherwise specified, the reagents and medicines used in the following examples and experiments are all conventional commercially available products.

[0042] It should be noted that, unless otherwise specified, the operations used in the following embodiments and experiments are all conventional operations in the art.

[0043] The experimental reagents used in the following examples are shown in Table 1.

[0044] Table 1 Experimental Drugs

[0045]

[0046]

[0047] The experimental instruments used in the following embodiments are shown in Table 2.

[0048] Table 2 Experimental Instruments

[0049] Electronic balance JM-B Yaoshi Jiming Weighing and Calibration Equipment Co., Ltd. Tungsten filament scanning electron microscope SU3500 Hitachi High Technology Company Video optical contact angle tester OCA20 DatapHysics Magnetic heating stirrer CJJ-6 Dadi Automation Instrument Factory, Jintan City, Jiangsu Province Damp heat aging test chamber SDJ6025 Chongqing Yinhe Test Instrument Co., Ltd. Sartorius Popular pH Meter PB-10 Shanghai Precision Scientific Instruments Co., Ltd. Flexural endurance tester DC-MIT135B Sichuan Changjiang Paper Instrument Co., Ltd. Computer-controlled universal material testing instrument QT-1136 Gaotai Testing Instruments Co., Ltd. Mid-infrared-far-infrared spectrometer Frontier PerkinElmer Thermogravimetric analyzer Themys one French Seymour

[0050] Example 1

[0051] The iron salt blueprint paper reinforcing agent provided in this embodiment includes the following raw materials: 1.8g ethyl cellulose powder, 20mL ethyl acetate, 20mL acetone, 20mL n-butanol reagent and 30μL antioxidant DPOP solution.

[0052] In this embodiment, the preparation method of the iron salt blueprint paper reinforcing agent includes the following steps:

[0053] S1. Take ethyl cellulose, organic solvent and antioxidant according to the stated mass proportions.

[0054] In this embodiment, 1.8g of ethyl cellulose powder, 20mL of ethyl acetate, 20mL of acetone, 20mL of n-butanol reagent and 30μL of antioxidant DPOP solution were weighed.

[0055] S2. Weigh 1.8g of ethyl cellulose powder, weigh 20mL of ethyl acetate, 20mL of acetone, and 20mL of n-butanol reagent, put them into a three-necked flask, add a reflux condenser, and stir with a magnetic stirrer until the ethyl cellulose is completely dissolved.

[0056] In this embodiment, the water bath heating temperature is set at 50°C and the stirring speed is 350 r / min.

[0057] S3. Measure 10 mL of the prepared ethyl cellulose solution into a 25 mL beaker. Use a pipette with a volume of 100 μL to take 30 μL of the antioxidant DPOP solution and add it to the ethyl cellulose solution to prepare a 0.3% DPOP solution. Place the solution in a magnetic stirrer and stir until homogeneous. Set the bath heating temperature to 40℃ and the stirring speed to 300 r / min until the mixture is homogeneous to obtain the reinforcing agent.

[0058] Example 2

[0059] The iron salt blueprint paper reinforcing agent provided in this embodiment includes the following raw materials: 1.8g ethyl cellulose powder, 20mL ethyl acetate, 20mL acetone, 20mL n-butanol reagent and 50μL antioxidant DPOP solution.

[0060] In this embodiment, the preparation method of the iron salt blueprint paper reinforcing agent includes the following steps:

[0061] S1. Take ethyl cellulose, organic solvent and antioxidant according to the stated mass proportions.

[0062] In this embodiment, 1.8g of ethyl cellulose powder, 20mL of ethyl acetate, 20mL of acetone, 20mL of n-butanol reagent and 50μL of antioxidant DPOP solution were weighed.

[0063] S2. Weigh 1.8g of ethyl cellulose powder, weigh 20mL of ethyl acetate, 20mL of acetone, and 20mL of n-butanol reagent, put them into a three-necked flask, add a reflux condenser, and stir with a magnetic stirrer until the ethyl cellulose is completely dissolved.

[0064] In this embodiment, the water bath heating temperature is set at 50°C and the stirring speed is 350 r / min.

[0065] S3. Measure 10 mL of the prepared ethyl cellulose solution into a 25 mL beaker. Use a pipette with a volume of 100 μL to take 50 μL of the antioxidant DPOP solution and add it to the ethyl cellulose solution to prepare a 0.5% DPOP solution. Place the solution in a magnetic stirrer and stir until homogeneous. Set the bath heating temperature to 40℃ and the stirring speed to 300 r / min until the mixture is homogeneous to obtain the reinforcing agent.

[0066] Example 3

[0067] The iron salt blueprint paper reinforcing agent provided in this embodiment includes the following raw materials: 1.8g ethyl cellulose powder, 20mL ethyl acetate, 20mL acetone, 20mL n-butanol reagent and 80μL antioxidant DPOP solution.

[0068] In this embodiment, the preparation method of the iron salt blueprint paper reinforcing agent includes the following steps:

[0069] S1. Take ethyl cellulose, organic solvent and antioxidant according to the stated mass proportions.

[0070] In this embodiment, 1.8g of ethyl cellulose powder, 20mL of ethyl acetate, 20mL of acetone, 20mL of n-butanol reagent and 80μL of antioxidant DPOP solution were weighed.

[0071] S2. Weigh 1.8g of ethyl cellulose powder, weigh 20mL of ethyl acetate, 20mL of acetone, and 20mL of n-butanol reagent, put them into a three-necked flask, add a reflux condenser, and stir with a magnetic stirrer until the ethyl cellulose is completely dissolved.

[0072] In this embodiment, the water bath heating temperature is set at 50°C and the stirring speed is 350 r / min.

[0073] S3. Measure 10 mL of the prepared ethyl cellulose solution into a 25 mL beaker. Use a pipette with a volume of 100 μL to take 80 μL of the antioxidant DPOP solution and add it to the ethyl cellulose solution to prepare a 0.8% DPOP solution. Place the solution in a magnetic stirrer and stir until homogeneous. Set the bath heating temperature to 40℃ and the stirring speed to 300 r / min until the mixture is homogeneous to obtain the reinforcing agent.

[0074] Example 4

[0075] The iron salt blueprint paper reinforcing agent provided in this embodiment includes the following raw materials: 1.8g ethyl cellulose powder, 20mL ethyl acetate, 20mL acetone, 20mL n-butanol reagent and 100μL antioxidant DPOP solution.

[0076] In this embodiment, the preparation method of the iron salt blueprint paper reinforcing agent includes the following steps:

[0077] S1. Take ethyl cellulose, organic solvent and antioxidant according to the stated mass proportions.

[0078] In this embodiment, 1.8g of ethyl cellulose powder, 20mL of ethyl acetate, 20mL of acetone, 20mL of n-butanol reagent and 100μL of antioxidant DPOP solution were weighed.

[0079] S2. Weigh 1.8g of ethyl cellulose powder, weigh 20mL of ethyl acetate, 20mL of acetone, and 20mL of n-butanol reagent, put them into a three-necked flask, add a reflux condenser, and stir with a magnetic stirrer until the ethyl cellulose is completely dissolved.

[0080] In this embodiment, the water bath heating temperature is set at 50°C and the stirring speed is 350 r / min.

[0081] S3. Measure 10 mL of the prepared ethyl cellulose solution into a 25 mL beaker. Use a pipette with a volume of 100 μL to take 100 μL of the antioxidant DPOP solution and add it to the ethyl cellulose solution to prepare a 1.0% DPOP solution. Place the solution in a magnetic stirrer and stir until homogeneous. Set the bath heating temperature to 40℃ and the stirring speed to 300 r / min until the mixture is homogeneous to obtain the reinforcing agent.

[0082] Comparative Example 1

[0083] The coating material provided in this comparative example includes the following raw materials: 1.8g ethyl cellulose powder, 20mL ethyl acetate, 20mL acetone, and 20mL n-butanol reagent.

[0084] In this comparative example, the preparation method of the reinforcing agent includes the following steps:

[0085] S1. Take ethyl cellulose, organic solvent and antioxidant according to the stated mass proportions.

[0086] In this embodiment, 1.8g of ethyl cellulose powder, 20mL of ethyl acetate, 20mL of acetone, 20mL of n-butanol reagent and 30μL of antioxidant DPOP solution were weighed.

[0087] S2. Weigh 1.8g of ethyl cellulose powder, weigh 20mL of ethyl acetate, 20mL of acetone, and 20mL of n-butanol reagent, put them into a three-necked flask, add a reflux condenser, and stir with a magnetic stirrer until the ethyl cellulose is completely dissolved.

[0088] In this embodiment, the water bath heating temperature is set at 50°C and the stirring speed is 350 r / min.

[0089] To verify the performance advantages of the iron salt blueprint paper reinforcement agent of the present invention, the following tests were conducted using the iron salt blueprint paper reinforcement agents provided in the examples and comparative examples.

[0090] Experiment 1: Thermogravimetric curve test of different iron salt blueprint reinforcement agents

[0091] Test samples: The reinforcing agent of Comparative Example 1, wherein the antioxidant content is 0%; the reinforcing agents of Examples 1 to 4, wherein the antioxidant DPOP content is 0.3%, 0.5%, 0.8% and 1.0% respectively. The reinforcing agents of Comparative Example 1 and Examples 1 to 4 are respectively referred to as Sample 1, Sample 2 to Sample 5.

[0092] The experimental procedure was as follows: 5 ml of each of the five samples was taken and dropped into a 50*50*2mm square silicone mold. After standing at a constant temperature of 25℃ for 48 hours, the five different reinforcing agent films were obtained by demolding with tweezers.

[0093] Thermal stability analysis was performed using a Themys One thermogravimetric analyzer from Cetram, France. 5–10 mg of sample film was weighed and placed in an α-Al₂O₃ crucible. The crucible was then placed in the thermogravimetric analyzer, with a heating rate of 20 °C / min and a temperature range of 30 °C–600 °C. The analyzer was placed in an air atmosphere. The results are as follows: Figure 1 As shown.

[0094] Figure 1 The thermogravimetric curves (TG) were measured under air atmosphere. The TG curves show that regardless of the concentration of antioxidant DPOP, a mass loss occurs around 300℃. The thermogravimetric curves of the blank control group (containing only ethyl cellulose) and the four groups containing antioxidant DPOP show similar trends, indicating that DPOP does not decompose into other substances in this temperature range. The mass loss is essentially complete at 550℃ in all five experimental groups. The blank control group without antioxidants shows a mass loss as high as 86.6% at 500℃, while the 0.8%-DPO mass loss is over 78%. Furthermore, at 350℃, when the mass loss rate is highest, the blank control group without antioxidants shows a mass loss of 78.2%, while the 0.8%-DPO and 1.0%-DPOP mass losses are around 65%. Other concentrations of DPOP contribute to reducing mass loss to varying degrees. Therefore, antioxidant DPOP contributes to the thermal stability of the binder, with the 0.8%-DPOP and 1.0%-DPOP showing more significant effects compared to the other two groups.

[0095] Through comprehensive comparison, the consolidating agent material (consolidating agent 4) in Example 1 has a good film-forming effect and is most suitable as a consolidating agent for the protection of iron salt blueprints. It can improve the heat resistance of cultural relics and achieve the expected protection effect.

[0096] Experiment 2: Whiteness characterization of different consolidating agents

[0097] Test samples: Comparative Example 1, Sample 1, Sample 2 to Sample 5 corresponding to Examples 1 to 4.

[0098] The experimental procedure is as follows: Prepare analytical grade ferric ammonium citrate and potassium ferricyanide reagents, beakers, glass rods, droppers, brown reagent bottles, brushes, an electronic balance with an accuracy of 0.1g, a tray, an acrylic plate, deionized water, and other reagents and instruments. The entire experimental operation should be carried out in a dark room without sunlight. Preparation of photosensitizers A and B: Photosensitizer A: Dissolve 40g of ferric ammonium citrate in 200mL of water to obtain a dark brown solution. After the solid sample is completely dissolved, place it in a brown reagent bottle. Photosensitizer B: Dissolve 16g of potassium ferricyanide in 200mL of water to obtain a yellow solution. After the solid sample is completely dissolved, place it in a brown reagent bottle. Take appropriate amounts of photosensitizer A and photosensitizer B and mix them thoroughly to obtain a deep yellow-green photosensitizer mixture with Prussian yellow as the component. Use a brush to apply an appropriate amount of the photosensitizer mixture evenly to the surface of paper in a vertical-to-horizontal order. After applying the photosensitive agent, place the paper coated with the agent in a dark or low-light condition to dry, obtaining photographic paper. Fix the photographic paper in the middle using two acrylic plates, expose it in a UV darkroom for 10 minutes, and then rinse the exposed paper with water for 10 minutes, ensuring the highlights are white and there is no yellow-green residue in the water. Place the paper on a plastic sheet to dry, obtaining iron salt photosensitive paper.

[0099] Take 5 ml of the above sample and brush it evenly onto the self-made iron salt blueprint paper to prepare 5 sets of blueprint paper simulation samples. Then, test them with the original untreated blueprint paper samples.

[0100] According to the national standard GB / 22894-2008, five sets of simulated blueprint samples and original blueprint paper samples were subjected to accelerated damp heat aging tests. Aging conditions: set temperature 80℃, humidity 65%, time 72h. After removing the blueprint paper samples, they were equilibrated indoors for two days. The five sets of aged simulated blueprint paper samples and original blueprint paper samples were then tested.

[0101] Test Method: The WSB-2 digital whiteness meter (Shanghai Pingxuan Scientific Instruments Co., Ltd.) was zeroed using a black tube, and then calibrated using a standard white board with a whiteness value of 81.5. According to the standard "Determination of Whiteness of Paper and Paperboard (CIE), D65 / 10°" (GB / T22880-2008), the whiteness of the paper before and after reinforcement was tested using the whiteness meter. Ten parallel experiments were performed on the same sample, and the relative error should be less than 5%. Results are as follows: Figure 2 As shown.

[0102] See Figure 2As shown, the whiteness value before the accelerated aging treatment was not significantly related to whether a reinforcing agent was applied, but depended on the preparation and rinsing process of the photosensitive liquid during the preparation of the iron salt blueprint paper. After the accelerated aging treatment, the whiteness of the iron salt blueprint paper samples decreased. The whiteness value of the untreated blueprint paper sample decreased by 2.5%, and the whiteness values ​​of samples 1 to 5 decreased by 1.5%, 2%, 1.7%, 1.3%, and 2.3%, respectively. This indicates that the reinforcing agent has a certain mitigating effect on the reduction of the whiteness value of the blueprint paper, and the 0.8%-DPOP treatment has the best mitigating effect on the reduction of whiteness.

[0103] Experiment 3: Microstructure testing of thin films with different reinforcing coating materials

[0104] Test samples: Samples 1, 2 to 5 from Test 2. Prepared blueprint paper simulation samples and original blueprint paper samples, as well as five groups of blueprint paper simulation samples and original blueprint paper samples after aging.

[0105] Experimental Method: Color difference was measured using an X-RiteVS-450 spectrophotometer. The CIE L*a*b color coordinate system was used to characterize the color change of the blueprint paper samples before and after accelerated aging under damp heat. L*, a*, and b* represent the measurements of luminance, hue, and saturation, respectively. The smaller the measured color difference ΔE, the smaller the color change at the same point on the blueprint paper sample before and after aging; conversely, the larger the ΔE, the greater the color change. The formula for calculating the color difference value in the CIE L*a*b color system is as follows:

[0106] ΔE * =[(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 ] 1 / 2

[0107] In the formula: ΔL*=L 老化后 -L* 老化前 (ΔL* represents the difference in brightness)

[0108] Δa*=a 老化后 -a* 老化前 (Δa* represents the red-green color deviation)

[0109] Δb*=b 老化后 -b* 老化前 (Δb* represents the yellow-blue deviation)

[0110] The results are shown in Table 3.

[0111] Table 3 Color difference of blueprint paper before and after aging

[0112] Blueprint Sample 6.12 Sample 1 5.82 Sample 2 4.17 Sample 3 3.66 Sample 4 1.74 Sample 5 2.71

[0113] As shown in Table 3, after accelerated aging under damp heat, the color difference value of the untreated blueprint paper sample was 6.12, indicating significant discoloration; the color difference value of Sample 1, with only ethyl cellulose added, was 5.82, indicating slight discoloration, suggesting that ethyl cellulose had virtually no effect on protecting the blueprint paper from color changes; the color difference values ​​of Samples 2 and 3 were 4.17 and 3.66, respectively, indicating slight discoloration; and the color difference values ​​of Samples 4 and 5 were 1.74 and 2.71, respectively, indicating very slight discoloration. This indicates that the antioxidant DPOP can inhibit the color change of iron salt blueprint paper, with 0.8% DPOP showing the best effect.

[0114] Experiment 4, Infrared Spectroscopy Analysis

[0115] Test samples: simulated blueprints and original blueprints prepared from samples 1 to 5 in test 2, as well as five sets of simulated blueprints and original blueprints after aging.

[0116] Test method: Sample 1 before and after reinforcement, and samples 1 to 5 before and after the damp heat accelerated aging test were subjected to 4000 nm using a PE-Frontier mid-infrared-far-infrared spectrometer. -1 ~400cm -1 The infrared spectrum of the sample was measured within the specified range, and the results are as follows: Figure 3 As shown.

[0117] See Figure 3 The infrared spectrum shows that the peak positions before and after coating with ethyl cellulose are basically the same, but the absorption peak intensities have changed. No new functional groups are formed, indicating that ethyl cellulose itself does not react with the iron salt blueprint paper, which is in line with the principles of cultural relic preservation. 3400cm -1 The absorption peak at 2900 cm⁻¹ is the OH stretching vibration peak. -1 The absorption peak at 1740 cm⁻¹ is due to the stretching vibrations of CH and CH₂ in the molecule. -1 The absorption peak at 1434 cm⁻¹ is the C=O stretching vibration peak. -1 and 1372cm -1 The absorption peak at 1020 cm⁻¹ is due to the bending vibration of the methylene group. -1 The absorption peak at 880 cm⁻¹ is the stretching vibration peak of CO. -1 917cm -1 The absorption peak is generated by the vibrational absorption peak of the OC2H3 functional group of ethyl cellulose.

[0118] Figure 3 Comparison of the infrared spectra of blueprinted paper before and after aging with ethyl cellulose reinforced with different concentrations of DPOP (b, c, d, e, and f) shows that the peak position did not change significantly, with the peak at 3400 cm⁻¹ remaining the same. -1~3300cm -1 The peak at position 0.8% is the OH stretching vibration peak. The peak intensity of sample 4, with 0.8%-DPOP, decreased the least before and after aging, indicating that the fiber bonding force of the blueprint paper decreased little after aging treatment, and the durability remained good. This concentration of reinforcing agent applied to the blueprint paper can ensure that it is minimally affected by high temperature and high humidity environments, and protect the information carried on the blueprint paper from damage to the greatest extent.

[0119] Experiment 5: Microscopic morphology test

[0120] Test samples: blueprint paper simulation samples prepared from samples 1 to 5 in test 2, and five groups of blueprint paper simulation samples after aging.

[0121] Experimental Method: Samples 1 to 5, before and after damp heat aging, were fixed on a cross-sectional test stage using conductive adhesive. The surfaces were then sputtered with gold for 120 seconds using an ion sputtering apparatus. The surface morphology was then observed at a certain magnification using a SU3500 tungsten filament scanning electron microscope. The microstructure of the samples at 200 μm under the tungsten filament scanning electron microscope is shown below. Figure 4 As shown, where: a1: unaged sample 1, a2: aged sample 1; b1: unaged sample 2, b2: aged sample; c1: unaged sample 3, c2: aged sample 3; d1: unaged sample 4, d2: aged sample 4; e1: unaged sample 5, e2: aged sample 5.

[0122] Depend on Figure 4 It can be seen that the paper fibers of the blueprint paper have a three-dimensional network structure, with each fiber interwoven and stacked, forming a large number of irregular gaps and pores on the surface, with Prussian blue pigment adhering to the fiber surface. After reinforcement, the Prussian blue pigment is tightly coated on the fibers, forming a thin film on the surface of the blueprint paper, making the pigment less likely to fall off. Furthermore, the reinforcing agent fills the gaps in the paper fibers to a certain extent, helping to improve the mechanical properties of the blueprint paper. After accelerated aging under humid heat, unreinforced blueprint paper experiences intensified hydrolysis of the paper cellulose and increased fiber breakage under high temperature and humidity conditions, while reinforced blueprint paper shows fewer fiber breaks and better film retention.

[0123] Experiment 6: Mechanical Performance Testing

[0124] Test samples: simulated blueprints and original blueprints prepared from samples 1 to 5 in test 2, as well as five sets of simulated blueprints and original blueprints after aging.

[0125] Test method: The simulated samples of samples 1 to 5 before and after hygrothermal accelerated aging were cut into strips with a width of (15±0.1) mm and a length of 130 mm. After equilibration in an environment with a temperature of 25℃ and a humidity of 35% for 3 days, the tensile strength and folding endurance of the paper were tested.

[0126] ①Tensive strength test

[0127] According to GB / T12914-2008 "Determination of Tensile Strength of Paper and Paperboard", the tensile strength of paper samples was tested using the constant-speed tensile method. Paper samples before and after hygrothermal accelerated aging were vertically clamped between two clamps with a gauge length of 100 mm and a constant tensile speed of 20 mm / min. Ten sets of measurements were taken for each type of paper sample before and after hygrothermal accelerated aging, and the average value was taken.

[0128] ② Flexural endurance test

[0129] According to GB / T457-2008 "Determination of Folding Endurance of Paper and Paperboard", the folding endurance of paper was tested using a paper folding endurance tester. An LB-MIT135 paper folding endurance tester was used to test the paper before and after aging, with a weight of 4.91 N. Ten sets of samples were tested before and after accelerated aging under damp heat, and the average value was taken.

[0130] The folding endurance of samples 1-5 before and after the accelerated aging test under damp heat is as follows: Figure 5 As shown, the tensile strength is as follows Figure 6 As shown.

[0131] Depend on Figure 5 It can be seen that the folding endurance of samples 1 to 5 after treatment was higher than that of the original blueprint paper samples, indicating that the mechanical properties of the samples were enhanced after ethyl cellulose film formation. After the accelerated aging treatment with damp heat, the folding endurance of the paper decreased. The folding endurance of the original blueprint paper sample decreased by 56%, while the folding endurance of samples 1 to 5 decreased by 42.9%, 22.8%, 33.3%, 14.3%, and 25%, respectively. The folding endurance of samples 1 to 5 decreased less than that of the original blueprint paper sample.

[0132] Depend on Figure 6 It can be seen that the tensile strength of samples 1 to 5 after treatment is higher than that of the original blueprint paper samples. After the hygrothermal accelerated aging treatment, the tensile strength of the blueprint paper decreased. The tensile strength of the original blueprint paper decreased by 1.28 kN / m, while the tensile strength of samples 1 to 5 decreased by 1.05 kN / m, 0.51 kN / m, 0.65 kN / m, 0.49 kN / m, and 1.12 kN / m, respectively. The decrease in tensile strength of samples 1 to 5 was less than that of the original blueprint paper.

[0133] Based on the changes in folding endurance and tensile strength, it can be inferred that the overall mechanical properties of the treated samples 1 to 5 are better preserved than those of the untreated blueprint paper. Ethyl cellulose can enhance the hydrogen bonds between fibers, thereby improving the mechanical properties of the paper, while the antioxidant DPOP can protect the paper under aging conditions and improve the weather resistance of the blueprint paper. Among them, 0.8% DPOP has the best effect.

[0134] Test 7, Contact Angle Test

[0135] The contact angle is the angle between the solid and liquid interface. The larger the contact angle, the stronger the hydrophobicity of the solid surface; the smaller the contact angle, the stronger the hydrophilicity. For the preservation of paper artifacts, good hydrophobicity can prevent the artifacts from being eroded by moisture in the preservation environment.

[0136] Test samples: simulated blueprints and original blueprints prepared from samples 1 to 5 in test 2, as well as five sets of simulated blueprints and original blueprints after aging.

[0137] Experimental Method: The static contact angle of blueprint paper before and after accelerated hygrothermal aging was measured using the seated drop method in a video optical contact angle meter. Strips of blueprint paper were cut and placed on a sample stage. Two microliters of deionized water were then dropped onto the surface of the paper sample. A suitable light intensity was adjusted, and a camera was used to quickly capture the surface image of the water droplet. The computer automatically performed fitting calculations to obtain the static contact angle value of the sample. Ten sets of measurements were taken for each sample, and the average value was calculated. The results are shown below. Figure 7 As shown.

[0138] Depend on Figure 7 It can be seen that the contact angles of samples 1 to 5 were all larger than those of the blueprint paper sample, increasing by 10.9°, 21.5°, 15°, 12.4°, and 6.6° respectively. The contact angle of the blueprint paper sample decreased significantly after 60 seconds, decreasing by 15.2°. However, the contact angle changes of samples 1 to 5 after the reinforcement treatment were all within 5° after 60 seconds, indicating that the hydrophobicity of the blueprint paper sample was significantly enhanced after treatment with ethyl cellulose reinforcement. After accelerated aging under humid heat, the adhesion between paper fibers decreased, and the antioxidant was partially consumed, resulting in a decrease in the contact angle of all samples. The original blueprint paper sample saw a decrease of 12.1°; the contact angles of samples 1 to 5 decreased by 2.3°, 12.5°, 6.9°, 0.6°, and 5° respectively. After 60 seconds, the contact angle of the aged blueprint paper sample decreased by 26.1°; the contact angles of samples 1 to 5 decreased by 2°, 1°, 6°, 2.4°, and 1.7° respectively. The test results show that the ethyl cellulose reinforcer with added DPOP has a significant protective effect on blueprint paper. It effectively improves the hydrophobicity of the blueprint paper itself, making it less susceptible to structural damage from water molecules during long-term storage. This prevents problems such as bleeding, blurring, and smudging of the blueprint paper content, thus preserving the information it carries. Among the blueprint paper, the ethyl cellulose protectant with 0.8% DPOP showed the smallest change in contact angle after damp heat aging treatment, indicating the best protective effect.

[0139] Experiment 8: Optimal selection test of antioxidants.

[0140] In order to select the best antioxidant among several antioxidants, different types of antioxidants were dissolved in ethyl cellulose solution and prepared into a reinforcing agent with a mass fraction of 0.8% according to the raw material ratio of Example 3.

[0141] The selected antioxidants are: antioxidant DPOP, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1010), n-octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), tris(2,4-di-tert-butyl)phosphite (antioxidant 168), and triethylene glycol ether-di(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate (antioxidant XH-245).

[0142] A new batch of iron salt blueprint paper was prepared using the method described in Experiment 2. Then, reinforcing agents prepared with different antioxidants were applied to the iron salt blueprint paper, and a damp heat accelerated aging test was conducted. The aging conditions were: temperature 80℃, humidity 65%, and time 72 hours. After removing the blueprint paper samples, they were equilibrated indoors for two days. Color difference and whiteness tests were performed on the iron salt blueprint paper samples before and after damp heat accelerated aging.

[0143] (1) The color difference of different antioxidants applied to the same position of the blueprint paper before and after aging is shown in Table 4 below. The color difference of the untreated paper after aging is 6.38.

[0144] Table 4. Color difference of blueprint paper coated with different antioxidants before and after aging.

[0145] Antioxidant DPOP 1.92 Antioxidant 1010 3.29 Antioxidant 1076 6.33 Antioxidant 168 2.75 Antioxidant XH-245 5.01

[0146] As shown in Table 4, the color difference of the iron salt blueprint paper coated with antioxidant DPOP was the smallest at 1.92. Color difference is the most significant data reflecting the change of iron salt blueprint paper before and after aging. The smaller the color difference value, the smaller the color change of the blueprint paper under high temperature and high humidity conditions and the better the retention. This indicates that antioxidant DPOP has a significant mitigating effect on the color change of iron salt blueprint paper compared with the other four antioxidants.

[0147] (2) The whiteness of the same location on the blueprint paper before and after aging, with different antioxidants applied, is as follows: Figure 8 As shown.

[0148] Depend on Figure 8 It can be seen that the whiteness of the iron salt blueprint samples coated with different antioxidants decreased after accelerated aging under humid heat. The decreases were as follows: DPOP by 0.4%, 1010 by 1.9%, 1076 by 2.2%, 168 by 2.0%, and XH-245 by 2.0%. This indicates that DPOP-based reinforcement treatment had the best effect in mitigating the whiteness reduction.

[0149] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. The application of a modified ethyl cellulose reinforcing agent in the reinforcement and protection of iron salt blueprint paper, characterized in that, The preparation method of the modified ethyl cellulose reinforcing agent includes the following steps: Step 1: Weigh 1.8g of ethyl cellulose powder, weigh 20mL of ethyl acetate, 20mL of acetone, and 20mL of n-butanol reagent, put them into a three-necked flask, add a reflux condenser, and stir with a magnetic stirrer until the ethyl cellulose is completely dissolved. Set the water bath heating temperature to 50℃ and the stirring speed to 350r / min. Step 2: Measure 10 mL of the prepared ethyl cellulose solution into a 25 mL beaker. Use a pipette with a volume of 100 μL to take 50 μL of the antioxidant DPOP solution and add it to the ethyl cellulose solution to prepare a 0.5% DPOP solution. Place the solution in a magnetic stirrer and stir until homogeneous. Set the bath heating temperature to 40℃ and the stirring speed to 300 r / min until the mixture is homogeneous to obtain the modified ethyl cellulose reinforcing agent.

2. The application of a modified ethyl cellulose reinforcing agent in the reinforcement and protection of iron salt blueprint paper, characterized in that, The preparation method of the modified ethyl cellulose reinforcing agent includes the following steps: Step 1: Weigh 1.8g of ethyl cellulose powder, weigh 20mL of ethyl acetate, 20mL of acetone, and 20mL of n-butanol reagent, put them into a three-necked flask, add a reflux condenser, and stir with a magnetic stirrer until the ethyl cellulose is completely dissolved. Set the water bath heating temperature to 50℃ and the stirring speed to 350r / min. Step 2: Measure 10 mL of the prepared ethyl cellulose solution into a 25 mL beaker. Use a pipette with a volume of 100 μL to take 80 μL of the antioxidant DPOP solution and add it to the ethyl cellulose solution to prepare a 0.8% DPOP solution. Place the solution in a magnetic stirrer and stir until homogeneous. Set the bath heating temperature to 40℃ and the stirring speed to 300 r / min until the mixture is homogeneous to obtain the modified ethyl cellulose reinforcing agent.

3. The application of a modified ethyl cellulose reinforcing agent in the reinforcement and protection of iron salt blueprint paper, characterized in that, The preparation method of the modified ethyl cellulose reinforcing agent includes the following steps: Step 1: Weigh 1.8g of ethyl cellulose powder, weigh 20mL of ethyl acetate, 20mL of acetone, and 20mL of n-butanol reagent, put them into a three-necked flask, add a reflux condenser, and stir with a magnetic stirrer until the ethyl cellulose is completely dissolved. Set the water bath heating temperature to 50℃ and the stirring speed to 350r / min. Step 2: Measure 10 mL of the prepared ethyl cellulose solution into a 25 mL beaker. Use a pipette with a volume of 100 μL to take 100 μL of the antioxidant DPOP solution and add it to the ethyl cellulose solution to prepare a 1.0% DPOP solution. Place the solution in a magnetic stirrer and stir until homogeneous. Set the bath heating temperature to 40℃ and the stirring speed to 300 r / min until the mixture is homogeneous to obtain the modified ethyl cellulose reinforcing agent.

Citation Information

Patent Citations

  • Black and white photo development reinforcing agent

    CN102786847A

  • Paper Buddhist text crisp powder pigment layer repairing liquid and repairing method

    CN106120455A